2007
DOI: 10.1093/aob/mcm227
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation of Cyclopia spp. (Leguminosae, Papilionoideae) by Burkholderia tuberum

Abstract: Papilionoid legumes from widely different tribes can be nodulated by beta-rhizobia, forming both indeterminate (Cyclopia) and determinate (Macroptilium) nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 25 publications
5
111
0
Order By: Relevance
“…Rhizobial Burkholderia have also been found in nodules of the papilionoid legumes Cyclopia and the herbaceous, perennial legume Rhynchosia ferulifolia, both endemic to the western Cape of South Africa (Elliott et al, 2007a;Garau et al, 2009). In this manuscript we describe additional Betaproteobacteria nodule bacteria from the wild perennial fynbos legume Lebeckia ambigua, which we reveal are novel species of Burkholderia.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Rhizobial Burkholderia have also been found in nodules of the papilionoid legumes Cyclopia and the herbaceous, perennial legume Rhynchosia ferulifolia, both endemic to the western Cape of South Africa (Elliott et al, 2007a;Garau et al, 2009). In this manuscript we describe additional Betaproteobacteria nodule bacteria from the wild perennial fynbos legume Lebeckia ambigua, which we reveal are novel species of Burkholderia.…”
Section: Introductionmentioning
confidence: 79%
“…1 and S2), previously isolated from Aspalathus carnosus (Moulin et al, 2001;Vandamme et al, 2002) and shown to be effective on several Cyclopia species (Elliott et al, 2007a). All strains in group four, except WSM4205, originate from sites 10 and 11.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some species of the Burkholderia genus were proven to be capable of establishing symbiosis with legume species, and are considered as beta-rhizobia (Moulin et al 2001;Elliott et al 2007). Burkholderia fungorum strains showed efficiency in nitrogen fixation in free-living conditions, and calcium phosphate and aluminum solubilization (OliveiraLongatti et al 2013;2014) and also were proved to present nodulation ability in Phaseolus vulgaris .…”
Section: Discussionmentioning
confidence: 99%
“…However, B. tuberum STM678 T and related South African strains which nodulate papilionoid legumes and which cannot nodulate Mimosa, appear to be more closely-related to Alpha-rhizobia and are distant from other beta-rhizobia in terms of their nod genes [5,[12][13][14][15][16]41]. Burkholderia species with nod genes that are related to B. tuberum STM678 T include B. sprentiae, B. rhynchosiae, B. dilworthii and B. dipogonis, as well as several other strains from papilionoid legumes from South Africa; the similarity in their nod genes suggests that they may have an origin common to some Alpha-rhizobia from papilionoid legumes, such as Bradyrhizobium.…”
mentioning
confidence: 99%